PENERAPAN ACCURATE 4 MANUFACTURE ACCOUNTING SYSTEM PADA PERENCANAAN PRODUKSI. - SAFRI SAFRI (JURNAL TEKNIK INDUSTRI, 2018)
Low quality factor, less attractive packaging, lack of product innovation, and inadequate location can be solved with improvement, but no less important is the effectiveness and efficiency, this factor is the key to compete in the current digital era, companies that can do both components will be able to survive in the market from outsider products that are relatively cheap. Accurate 4 with a bit of engineering by coding some menus can be done so that helps management and part production in determining the number of units to be produced explicitly. There is an inappropriate utilization of the accurate 4 module, but can be neutralized once the pre-load process has been completed by closing it on the prepared menu. The result of utilizing accurate 4 for production process makes production more scheduled so that effectiveness and efficiency can be done.Keywords: Accurate 4 Manufacture, effectiveness and efficiency coding.